C1-C2 screw fixation in the patient with anomalous course of vertebral artery – a case report - Ivetić, Dražen; Pavlićević, Goran; Antić, Branislav (Vojnosanitetski pregled, 2021)
Introduction. The atlantoaxial complex is a very complicated structure and open reduction of C1-C2 subluxation is very demanding. Atlantoaxial instability may result from the traumatic, inflammatory, neoplastic, congenital or degenerative disorders. Anatomy of the vertebral artery is essential for surgical approach and sometimes the placement of C2 pedicle screw is not possible. In these instances, the translaminar screw placement in C2 can provide an alternative fixation point in C2, without threatening injury to the vertebral artery. Case report. We presented 54- year-old patient with cervical myelopathy according to traumatic atlantoaxial subluxation. Computed tomography angiography showed a bilateral vertebral artery anomaly of “high-riding” type. The patient was operated and the posterior C1-C2 screws fixation was used. Due to the vertebral artery anomaly C2 screws were translaminary inserted. Complete reduction of C1-C2 subluxation and excellent neurological improvement were achieved. Conclusion. Surgical treatment of C1-C2 subluxation is very challenging. Many techniques of atlantoaxial fixation have been developed. The use of C2 translaminar screw is an alternative method of fixation in the treatment of atlantoaxial instability, especially in cases with the vertebral artery anomaly.